A Development of a Coarse Particle Concentration Measurement System Using a Crystal-Based Sensor and a Dust Sensor for Air Quality Measurement - Budianto, Arif; Rahayu, Susi; Mardiana, Laili; Ridho Illahi, Ramadian; Juniarti, Rosita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
QCM or quartz crystal microbalance is a non static crystal that can be used as a mass sensor. As a piezoelectric crystal, a QCM generates an electrical signal with a specific frequency. The frequency change can be utilized as a frequency counter in a mass measurement system. This study aims to develop a coarse particle sensor system using a QCM and an oscillator circuit. In line with this, this study uses an oscillator circuit and a QCM for a sensor development. Thus, the frequency measurement of the QCM contains an oscillator and a signal conditioner connected to a microcontroller. For this purpose, an Arduino Nano was used as the signal processing, while a QCM was used as a coarse particle sensor and compared to a digital dust sensor (Winsen ZH03). The sensor system was evaluated using a fixed-type crystal connected to an oscillator: 2.5 MHz - 7.2 MHz. Arduino Nano processed the frequency signal generated by the developed oscillator. The results show that the sensor system has a stable output signal compared to the comparator. There is a linear correlation between the frequency measured by the system and the oscilloscope (99.73%). It can be concluded that the sensor system can measure coarse particle concentrations from 32-620 ug/cm3 (frequencies from 2 MHz to 7.2 MHz) with a response time of 1 second. The system has an accuracy of 99% and a resolution of 1 Hz.